Taxonomic contribution to the genus Sphaerosyllis (Annelida: Syllidae: Exogoninae) in the Black Sea - Surugiu, Victor; Martín, Guillermo San (Zootaxa, 2017)
During a study of fauna associated with a shallow-water Zostera (Zosterella) noltei bed from the southern part of the Romanian Black Sea coast, among the identified material collected in 2015, a syllid polychaete belonging to the subfamily Exogoninae, Sphaerosyllis taylori Perkins, 1981, represents a new record for the Black Sea. Re-examination of available specimens previously identified as Sphaerosyllis bulbosa Southern, 1914 revealed that they belong to an unknown species, described herein as Sphaerosyllis pontica sp. nov. The new species is characterized by the median antenna inserted more posteriorly than the lateral antennae, dorsal cirri with bulbous bases and very short tips, shorter than the parapodial lobes, dorsal cirri absent on chaetiger 2, parapodial glands with fibrillar material from chaetiger 4 onwards, compound chaetae with short blades and smooth shafts, anterior parapodia with two aciculae each, one straight and one with bent tip. Descriptions of both species are provided together with a key to all Sphaerosyllis species known from the Black Sea.